High-temperature in-situ ceramifiable porous carbon ceramic material as well as preparation method and application thereof

By adding flux to the carbon-based resin matrix and ceramic precursor and performing hot pressing molding, high-temperature in-situ porcelain-able porous carbon-ceramic materials are prepared, which solves the problems of high thermal conductivity and ablation of existing porcelain-able materials. The problem of low thermal insulation performance is achieved by achieving better thermal insulation performance.

CN119350050APending Publication Date: 2025-01-24ZHONGSHAN INST OF CHANGCHUN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411551846.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing porcelain-encapsible materials have high thermal conductivity, resulting in poor ablation and thermal insulation performance.

Method used

By reacting the carbon -based resin matrix and ceramic front -drive body, the melting agent is added, and the thermal pressure molding is formed after the mechanical is mixed to form a high -temperature porcelain porous carbon pottery material.

Benefits of technology

The thermal conductivity of the material is reduced, the ablation insulation performance is improved, and the problems of high thermal conductivity and low ablation insulation performance of existing porcelain-able materials are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350050A_ABST
    Figure CN119350050A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal protection materials, in particular to a high-temperature in-situ ceramifiable porous carbon ceramic material as well as a preparation method and application thereof. According to the preparation method, a carbon-based resin matrix and a ceramic precursor are taken as main reaction raw materials, a fluxing agent is added, mechanical blending is carried out, and hot press molding is carried out in a hot melting state, so that a ceramic protection layer is formed on the surface of a carbon layer, and the high-temperature in-situ ceramifiable porous carbon ceramic material is prepared. According to the method, on the basis that the hot melting temperature of the raw materials is reduced, the heat conductivity of the high-temperature in-situ ceramifiable porous carbon ceramic material is reduced, the ablation heat insulation performance is improved, and the problems that an existing ceramifiable material is high in heat conductivity and low in ablation heat insulation performance are solved. The high-temperature in-situ ceramifiable porous carbon ceramic material can be used for preparing an ablative thermal insulation material, and meets the use performance requirements of the ablative thermal insulation material in the field of thermal protection at the temperature of 2500 DEG C or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat protection materials, and in particular to a high-temperature in-situ ceramicizable porous carbon ceramic material and a preparation method and application thereof. Background Art

[0002] Traditional polymer-based composite materials often undergo pyrolysis, melting or combustion at high temperatures, causing their performance to drop sharply, making them unable to meet the use requirements of new aircraft thermal protection systems in specific environments. Therefore, in order to meet the thermal insulation and lightweight requirements of new aircraft thermal protection systems, researchers have introduced ceramic technology based on the field of polymer-based composite materials, bringing new breakthroughs to materials science, especially in extreme environments such as high temperature, high pressure, and strong corrosion.

[0003] At present, a series of research results have been achieved in the field of ceramicization of polymer-based composite materials. For example, prior art 1: Publication No. CN102675822, a ceramicizable carbon-based polymer composite material is prepared by mixing carbon-based resin, fiber reinforcement material, high temperature resistant coupling agent, aluminosilicate mineral powder and non-oxide ceramic powder.

[0004] Prior art 2: Publication No. CN101215156 uses liquid organic siloxane as a ceramic precursor and solid organic polysiloxane as a molding mold. After cross-linking and curing by heating, light or standing, the cross-linking and curing are induced, and then pyrolysis is performed at 900°C to prepare silicon oxygen carbon ceramic products.

[0005] Prior art 3: Publication No. CN102167832, a ceramic material is formed by cross-linking a poly(carborane-siloxane / silazane) polymer at a temperature of 1000°C.

[0006] The above-mentioned prior art is limited to silicon polymers in terms of resin matrix, and the density of the material after ceramicization is relatively high, at 1.7g / cm 3 In addition, compared with the density of 1.5g / cm 3 The thermal conductivity of the ceramic material provided by the above-mentioned prior art is relatively high, resulting in poor ablation thermal insulation performance. Summary of the invention

[0007] In order to solve the problems of high thermal conductivity and low ablation thermal insulation performance of existing ceramic materials, the purpose of the present invention is to provide a high-temperature in-situ ceramic porous carbon ceramic material and its preparation method and use.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows.

[0009] The first aspect of the present invention provides a method for preparing a high-temperature in-situ ceramic porous carbon ceramic material, comprising the following steps:

[0010] A carbon-based resin matrix and a ceramic precursor are used as main reaction raw materials, a flux is added, and after mechanical blending, hot pressing is performed in a hot melt state to form a ceramic protective layer on the surface of the carbon layer, so as to obtain a high-temperature in-situ ceramic porous carbon ceramic material; the carbon-based resin matrix is ​​at least one of polyimide resin, aminophenolic resin, boron phenolic resin, barium phenolic resin, magnesium phenolic resin, polyurethane, and epoxy resin; the ceramic precursor is at least one of albite, cordierite, silicon carbide, and zirconium dioxide.

[0011] The present invention uses a carbon-based resin matrix to provide a carbon source, uses a ceramic precursor to provide a ceramic source, and conducts a high-temperature reaction through the carbon-based resin matrix and the ceramic precursor under the action of a flux to form a ceramic protective layer on the surface of the carbon layer to obtain a high-temperature in-situ ceramic porous carbon ceramic material. The method of the present invention can reduce the thermal conductivity of the high-temperature in-situ ceramic porous carbon ceramic material on the basis of reducing the hot melting temperature of the raw materials, and improve the ablation thermal insulation performance of the high-temperature in-situ ceramic porous carbon ceramic material, thereby solving the problem of high thermal conductivity and low ablation thermal insulation performance of the existing ceramic materials.

[0012] The role of mechanical blending in the present invention is to make the raw materials fully mixed and uniform, so as to ensure that a uniform ceramic protective layer can be obtained in the subsequent molding process. Hot pressing molding is carried out in a hot melt state. At this stage, the uniformly mixed raw materials are heated to a certain temperature to make them in a hot melt state. Then, molding is carried out under the action of high pressure, so that the ceramic precursor and the carbon-based resin matrix are closely combined together, and a dense ceramic protective layer is formed on the surface of the carbon layer.

[0013] Preferably, the mass ratio of the carbon-based resin matrix, the ceramic precursor and the flux is 3-4:4-5:0.8-1.

[0014] Preferably, the flux is at least one of cage-type organosilicon silsesquioxane, silicon dioxide, and bismuth oxide. The function of the flux is to improve the mixing uniformity of the raw materials and reduce the sintering temperature, thereby improving the efficiency and quality of the entire process.

[0015] Preferably, the conditions for hot pressing molding are: hot pressing temperature of 160° C. to 200° C.; hot pressing pressure of 5 MPa to 15 MPa; and hot pressing time of 3 h to 4 h.

[0016] In the present invention, within the range of hot pressing temperature of 160°C to 200°C, as the hot pressing temperature increases, the curing effect becomes better and the thermal properties of the product become higher. Since the product is a thermosetting polymer, a higher curing temperature will result in a higher degree of crosslinking, so its thermal properties become higher. However, when the hot pressing temperature is greater than 200°C, the carbon-based resin matrix decomposes. When the hot pressing temperature is less than 160°C, the carbon-based resin matrix does not melt, resulting in uneven dispersion of the mixture, the presence of an interface, and poor mechanical properties.

[0017] Preferably, before the hot pressing molding, the process further includes: vacuum degassing the hot-melt mixture.

[0018] In the present invention, the carbon-based resin matrix can provide good adhesion and plasticity; the ceramic precursor can be converted into a ceramic phase under specific conditions to form a protective layer. The carbon-based resin matrix is ​​at least one of polyimide resin, aminophenolic resin, boronphenolic resin, bariumphenolic resin, magnesiumphenolic resin, polyurethane, and epoxy resin.

[0019] Specifically, the synthesis process of the polyimide resin is:

[0020] 4,4'-oxydiphthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride and ethanol were added to a 3L three-necked round-bottom flask equipped with a reflux condenser and a mechanical stirring device in a molar ratio of 1:2:3, and the solid content was calculated to be 40%. The mixture was refluxed and stirred at 100°C for 4 hours to obtain a clear carboxylate solution. The carboxylate solution was cooled to below 40°C, and an ether-containing diamine was added, wherein the ether-containing diamine was 4,4'-diaminodiphenyl ether, and the molar ratio of 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether and 5-norbornene-2,3-dicarboxylic anhydride was 1:2:2. The mixture was heated to 100°C and refluxed and stirred for 2 hours. Afterwards, the reaction system was cooled to room temperature to obtain a brown-red polyimide resin. The weight average molecular weight of the polyimide resin was 2000 to 10000 Daltons.

[0021] The synthesis process of the boron phenolic resin is as follows: the mass of the raw materials used is calculated according to the molar ratio of phenol, formaldehyde and boric acid being 3:4.2:1, and phenol and boric acid are added to a three-necked round-bottom flask with a stirrer, a condenser and a water separator, and reacted at 160°C for 2 hours. During the process, vacuum is used to remove the water produced by the reaction to obtain boric acid ester. The reaction system is cooled to 60°C, and polyformaldehyde with a degree of polymerization of 8 is added. The chemical formula of polyformaldehyde with a degree of polymerization of 8 is (CH2O)8. The temperature is raised to 140°C and the reaction is continued for 1 hour. During the process, vacuum is used to remove the water produced by the reaction, and finally the temperature is lowered to room temperature to obtain a yellow boron-modified phenolic resin, referred to as BPR, with a yield of 60%. The weight average molecular weight of the boron phenolic resin is 1000-1500 Daltons.

[0022] The epoxy resin is a bisphenol A epoxy resin of model E-51 produced by China Petrochemical Group Baling Petrochemical Co., Ltd., with an epoxy value of 0.48-0.54 and a weight average molecular weight of 1000-10000 Daltons.

[0023] The polyurethane is an existing polyurethane resin, for example, a polyether polyurethane resin prepared in CN114773566B.

[0024] The magnesium phenolic resin is a thermosetting resin synthesized by reacting phenol and formaldehyde at 100° C. for 4 hours with magnesium oxide as a catalyst. The mass ratio of phenol, formaldehyde and magnesium oxide is 3:3.3:0.4.

[0025] The phenol-formaldehyde resin is a thermosetting resin synthesized by reacting phenol and formaldehyde at 90° C. for 5 hours with ammonia water as a catalyst. The mass ratio of phenol, formaldehyde and ammonia water is 3:3.6:0.8.

[0026] The barium phenolic resin is a thermosetting resin synthesized by reacting phenol and formaldehyde at 105° C. for 3 hours under the action of barium hydroxide as an alkaline catalyst. The mass ratio of phenol, formaldehyde and barium hydroxide is 3:3.5:0.5.

[0027] The second aspect of the present invention provides a high-temperature in-situ ceramic porous carbon ceramic material, which is prepared by the preparation method described in the first aspect.

[0028] Preferably, the average pore size of the high temperature in-situ ceramicizable porous carbon ceramic material is 5 nm to 100 μm.

[0029] Preferably, the high-temperature in-situ ceramicizable porous carbon ceramic material has a linear ablation rate of -0.05 mm / min and a mass ablation rate of 0.04 g / min.

[0030] The third aspect of the present invention provides a use of the high-temperature in-situ ceramicizable porous carbon ceramic material described in the second aspect in preparing ablative thermal insulation materials.

[0031] Preferably, the thermal protection temperature of the ablative heat-insulating material is between 2500°C and 3800°C.

[0032] Beneficial effects of the present invention:

[0033] 1. The present invention uses a carbon-based resin matrix to provide a carbon source, and a ceramic precursor to provide a ceramic source. The carbon-based resin matrix and the ceramic precursor react at high temperature under the action of a flux to form a ceramic protective layer on the surface of the carbon layer to obtain a high-temperature in-situ ceramic porous carbon ceramic material. The method of the present invention can reduce the thermal conductivity of the high-temperature in-situ ceramic porous carbon ceramic material on the basis of reducing the hot melting temperature of the raw materials, and improve the ablation thermal insulation performance of the high-temperature in-situ ceramic porous carbon ceramic material, thereby solving the problem of high thermal conductivity and low ablation thermal insulation performance of the existing ceramic materials.

[0034] 2. The high-temperature in-situ ceramic-forming porous carbon ceramic material of the present invention has excellent ablation and heat insulation properties, with a linear ablation rate of -0.05 mm / min and a mass ablation rate of 0.04 g / min; and the back temperature of a 5 mm sheet of high-temperature in-situ ceramic-forming porous carbon ceramic material is 85°C after oxyacetylene ablation for 6 minutes.

[0035] 3. The preparation method of the present invention is simple, easy to operate, and has a high product molding rate. It has the characteristics of high temperature resistance, ablation resistance and excellent thermal insulation performance, and can meet the performance requirements of ablative thermal insulation materials in the field of thermal protection above 2500°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a scanning electron microscope image of the PI-BE40 material of Example 1 after ablation at 2500°C.

[0037] Figure 2 It is the X-ray diffraction diagram of the materials of Example 1 and Comparative Examples 1 and 2 after ablation at 2500°C. Among them, B before ablation represents cage-type organosilicon silsesquioxane before ablation; E before ablation represents sodium feldspar before ablation; PI before ablation represents polyimide resin before ablation; PI-BE40 after ablation represents PI-BE40 material after ablation; PI-GF after ablation represents PI-GF material after ablation; PI-BE40-GF after ablation represents PI-BE40-GF material after ablation.

[0038] Figure 3 The EDS spectra of the materials of Example 1 and Comparative Examples 1 and 2 after ablation at 2500°C are shown in Figure 1. (a) is the EDS spectra of the ceramic protective layer of the PI-BE40 material of Example 1 after ablation at 2500°C; (b) is the EDS spectra of the carbon layer of the PI-BE40 material of Example 1 after ablation at 2500°C; (c) is the EDS spectra of the carbon layer of the PI-GF material of Comparative Example 1 after ablation at 2500°C; (d) is the EDS spectra of the carbon layer of the PI-BE40-GF material of Comparative Example 2 after ablation at 2500°C.

[0039] Figure 4 It is the thermal insulation performance curve of the high temperature in-situ porcelainizable porous carbon ceramic material of Example 4 to Example 6. Among them, PII represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 2000 to 3000 Daltons; PII-50 represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 4000 to 5000 Daltons; PII-100 represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 9000 to 10000 Daltons.

[0040] Figure 5 It is the thermal weight loss curve of the high temperature in-situ ceramic porous carbon ceramic material of Example 4 to Example 6. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0043] The technical solution of the present invention is further described below by means of specific examples. In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0044] In the following embodiments, the synthesis process of the polyimide resin is as follows: 4,4'-oxydiphthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride and ethanol are added to a 3L three-necked round-bottom flask equipped with a reflux condenser and a mechanical stirring device in a molar ratio of 1:2:3, and the solid content is calculated to be 40%. The mixture is refluxed and stirred at 100°C for 4 hours to obtain a clear carboxylate solution. The carboxylate solution is cooled to below 40°C, and an ether-containing diamine is added, wherein the ether-containing diamine is 4,4'-diaminodiphenyl ether, and the molar ratio of 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether and 5-norbornene-2,3-dicarboxylic anhydride is 1:2:2. The mixture is heated to 100°C and refluxed and stirred for 2 hours. Afterwards, the reaction system temperature is cooled to room temperature to obtain a brown-red ether-containing polyimide resin solution. The weight average molecular weight of the polyimide resin is 2,000 to 10,000 Daltons.

[0045] The synthesis process of boron phenolic resin is as follows: the mass of the raw materials used is calculated according to the molar ratio of phenol, formaldehyde and boric acid of 3:4.2:1, and phenol and boric acid are added to a three-necked round-bottom flask with a stirrer, a condenser and a water separator, and reacted at 160°C for 2 hours. During the process, vacuum is used to remove the water produced by the reaction to obtain boric acid ester. The reaction system is cooled to 60°C, and polyformaldehyde with a degree of polymerization of 8 is added. The chemical formula of polyformaldehyde with a degree of polymerization of 8 is (CH2O)8. The temperature is raised to 140°C and the reaction is continued for 1 hour. During the process, vacuum is used to remove the water produced by the reaction, and finally the temperature is reduced to room temperature to obtain a yellow boron-modified phenolic resin, referred to as BPR, with a yield of 60%. The weight average molecular weight of the boron phenolic resin is 1000-1500 Daltons.

[0046] The epoxy resin is a bisphenol A epoxy resin of model E-51 produced by China Petrochemical Group Baling Petrochemical Co., Ltd., with an epoxy value of 0.48-0.54 and a weight average molecular weight of 1000-10000 Daltons.

[0047] Albite was purchased from Shanghai Institute of Silicates.

[0048] In the following embodiments of the present invention, the full English name of polyimide resin is Polyimide resin, referred to as PI. The full English name of glass fiber is Glass Fiber, referred to as GF.

[0049] Example 1

[0050] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0051] (1) Weigh 40 g of albite, 50 g of polyimide resin, and 10 g of cage-type organosilicon silsesquioxane and add them to a high-speed mixer to mix and obtain a mixture. The weight average molecular weight of the polyimide resin is 2000 to 2500 Daltons.

[0052] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200°C and a hot pressing pressure of ≥5 MPa for 4 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material, which is recorded as PI-BE40.

[0053] Comparative Example 1

[0054] A method for preparing a porous composite material comprises the following steps:

[0055] (1) Weigh 50 g of polyimide resin and 50 g of glass fiber and add them to a high-speed mixer to mix and obtain a mixture. The weight average molecular weight of the polyimide resin is 2000-2500 Daltons. The glass fiber added in the embodiment of the present invention is used as a filler to improve the heat resistance and mechanical strength of the porous carbon ceramic material.

[0056] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot press pressure ≥5 MPa for 4 h, and then demolded to obtain a porous composite material, which is recorded as PI-GF.

[0057] Comparative Example 2

[0058] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0059] (1) Weigh 5 g of albite, 50 g of polyimide resin, 40 g of cage-type organosilicon silsesquioxane and 5 g of glass fiber and add them into a high-speed mixer to mix to obtain a mixture. The weight average molecular weight of the polyimide resin is 2000 to 2500 Daltons.

[0060] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot pressing pressure ≥5 MPa for 4 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material, which is recorded as PI-BE40-GF.

[0061] Table 1 Comparison of feeding conditions with different glass fiber addition amounts

[0062]

[0063] Note: B represents cage-type organosilicon silsesquioxane; E represents albite; PI represents polyimide resin; PI-BE40 represents polyimide resin + cage-type organosilicon silsesquioxane + 40% albite; GF represents glass fiber; PI-GF represents polyimide resin + glass fiber; PI-BE40-GF represents polyimide resin + cage-type organosilicon silsesquioxane + 40% albite + glass fiber.

[0064] Test 1: Dynamic ablation test.

[0065] The PI-BE40 material of Example 1, the PI-GF material of Comparative Example 1 and the PI-BE40-GF material of Comparative Example 2 were used as samples for dynamic ablation performance test, and compared with cage-type organosilicon silsesquioxane, albite and polyimide resin before ablation.

[0066] Test method: Dynamic ablation test was carried out using a Bunsen burner, with the flame 10 mm away from the sample, the ablation temperature 2500°C, and the ablation time 15 min.

[0067] Figure 1 This is a scanning electron microscope image of the PI-BE40 material of Example 1 after ablation at 2500°C.

[0068] pass Figure 1 Scanning electron microscope analysis shows that after the PI-BE40 material of Example 1 is ablated at 2500°C, the surface of the sample is harder. This is because the cage-type organosilicon silsesquioxane and albite can undergo a eutectic reaction under ablation conditions to generate a molten liquid phase. Under high-temperature ablation conditions, the molten liquid phase can wrap the carbon layer formed by the polyimide resin, and the surface diffusion of the molten liquid phase reduces the sintering energy, forming a dense ceramic protective layer on the surface of the carbon layer, which hinders the diffusion of oxygen from the boundary layer into the carbon-based resin matrix, thereby preventing the thermal decomposition reaction of the carbon-based resin matrix, thereby effectively fixing the polyimide resin pyrolytic carbon and preventing further erosion of the material by the high-temperature and high-pressure airflow.

[0069] Compared with Example 1, only glass fiber is added in Comparative Example 1. Although the addition of glass fiber can improve the heat resistance and mechanical strength of the PI-GF material, since no dense ceramic protective layer is formed on the surface of the carbon layer, the ablation thermal insulation performance of the PI-GF material is poor.

[0070] Compared with Example 1, Comparative Example 2 uses part of the glass fiber to replace the cage-type organosilicon silsesquioxane, which results in the ablation thermal insulation performance of the PI-BE40-GF material of Comparative Example 2 being relatively poor. However, compared with the PI-GF material of Comparative Example 1, the ablation thermal insulation performance of the PI-BE40-GF material of Comparative Example 2 is relatively good.

[0071] The results of the dynamic ablation experiment show that the thermal weight loss rate of the PI-BE40 material of Example 1 after ablation at 2500°C is less than 5%, and the dimensional change is less than 3%. The surface of the sample remains intact without stratification and obvious erosion or peeling.

[0072] After PI-BE40-GF of Comparative Example 2 was ablated at 2500°C, the thermal weight loss rate of the sample was less than 10%, the dimensional change of the sample was less than 5%, and the surface of the sample remained intact without delamination, obvious erosion, or peeling.

[0073] Compared with Comparative Example 2, after the PI-GF material of Comparative Example 1 was ablated at 2500°C, the thermal weight loss rate of the sample was greater than 15%, the size change of the sample was greater than 10%, and obvious erosion and peeling problems occurred on the surface of the sample.

[0074] Through the above analysis, it can be known that Example 1 of the present invention utilizes a carbon-based resin matrix to provide a carbon source, utilizes a ceramic precursor to provide a ceramic source, and uses the carbon-based resin matrix and the ceramic precursor to carry out a high-temperature reaction under the action of a flux to form a ceramic protective layer on the surface of the carbon layer, thereby obtaining a high-temperature in-situ ceramic-izable porous carbon ceramic material, thereby improving the ablation and thermal insulation properties of the high-temperature in-situ ceramic-izable porous carbon ceramic material.

[0075] Figure 2 It is the X-ray diffraction diagram of the materials of Example 1 and Comparative Examples 1 and 2 after ablation at 2500°C. Among them, B before ablation represents cage-type organosilicon silsesquioxane before ablation; E before ablation represents sodium feldspar before ablation; PI before ablation represents polyimide resin before ablation; PI-BE40 after ablation represents PI-BE40 material after ablation; PI-GF after ablation represents PI-GF material after ablation; PI-BE40-GF after ablation represents PI-BE40-GF material after ablation.

[0076] Depend on Figure 2It can be seen that the polyimide resin before ablation has only one diffuse diffraction peak, which indicates that the synthesized polyimide resin has a relatively low tendency to crystallize. This is mainly because the main chain of the polyimide resin molecule contains a large number of structures that increase the flexibility of the molecular chain, which reduces the crystallization tendency of the polymer. Amorphous polymers usually have lower softening temperatures and better solubility properties than other similar crystals.

[0077] At the same time, through the analysis of the XRD spectrum, it can be seen that the B and E characteristic peaks in the PI-BE40 material and PI-BE40-GF material after ablation almost disappeared, indicating that B and E underwent obvious amorphous transformation during the ablation process, generating an amorphous ceramic structure.

[0078] As for the PI-GF material after ablation, the X-ray diffraction analysis shows a more diffuse diffraction peak than the polyimide resin before ablation. This shows that ablation has an impact on the molecular structure of the polyimide resin, causing its crystallinity to further decrease and the amorphous characteristics to become more prominent. This is mainly because the arrangement of the molecular chains of the polyimide resin is more disordered during the ablation process.

[0079] The full name of EDS in English is Energy Dispersive Spectroscopy, and its Chinese name is Energy Dispersive Spectroscopy; EDS energy spectrum is also called X-ray energy spectrum analysis.

[0080] Figure 3 The EDS spectra of the materials of Example 1 and Comparative Examples 1 and 2 after ablation at 2500°C are shown in Figure 1. (a) is the EDS spectra of the ceramic protective layer of the PI-BE40 material of Example 1 after ablation at 2500°C; (b) is the EDS spectra of the carbon layer of the PI-BE40 material of Example 1 after ablation at 2500°C; (c) is the EDS spectra of the carbon layer of the PI-GF material of Comparative Example 1 after ablation at 2500°C; (d) is the EDS spectra of the carbon layer of the PI-BE40-GF material of Comparative Example 2 after ablation at 2500°C.

[0081] It can be seen from the EDS spectrum that the ceramic protective layer of the PI-BE40 material of Example 1 after ablation at 2500° C. is mainly silicate ceramic, wherein the Al content is 21%, the Si content is 11%, and the O content is 52%.

[0082] The main components of the carbon layer of the PI-BE40 material of Example 1 after ablation at 2500° C. are carbon and a small amount of silicon dioxide, wherein the C content is 52%, the O content is 30%, and the Si content is 17%.

[0083] The main components of the carbon layer of the PI-GF material of Comparative Example 1 after ablation at 2500° C. are carbon and silicon dioxide, wherein the C content is 20%, the O content is 50%, and the Si content is 30%.

[0084] The main components of the carbon layer of the PI-BE40-GF material of Comparative Example 2 after ablation at 2500° C. are silicate ceramics, in which the C content is 19%, the O content is 23%, and the Si content is 58%.

[0085] Figure 3 The EDS spectrum shows that B mainly contains elements such as C, O, and Si, and E mainly contains elements such as C, O, Na, and Al. It is determined that the main component of B is cage-type organosilicon silsesquioxane, and the main component of E is albite.

[0086] After ablation, the sample surfaces of PI-BE40 material and PI-BE40-GF material melted into a whole, and the residual structure was relatively compact. This was because during the ablation process, cage-type organosilicon silsesquioxane melted to form a liquid phase, which reacted with albite to form a eutectic, resulting in liquid phase sintering, which promoted the migration of cracking products and fillers and reduced the energy required for the reaction.

[0087] In addition, above the thermal cracking temperature of the resin, the activated carbon after the cracking of the resin can be used as a carbon source to reduce the sintering activation energy of the ceramic precursor and form carbon-reduced aluminate minerals and silicate minerals. Non-oxide ceramic powder, as a second phase particle dispersed in aluminosilicate, is conducive to the formation of aluminate microcrystals and silicate microcrystals, and finally forms a ceramic layer with a certain strength on the surface of the material, preventing the further diffusion of heat into the material. The surface micromorphology analysis of the material sample after ablation shows that the ceramic precursor can reduce the loss of carbon under ablation conditions and play a role in fixing the carbon source of the material. The EDS energy spectrum analysis of the ablated material shows that its main components are Al2O3, SiO2 and SiC, which proves that the ceramic precursor participates in the reaction during the ablation process and forms a hybrid material with the resin carbon at high temperature, thereby improving the ablation resistance and thermal insulation properties of the PI-BE40 material.

[0088] Example 2

[0089] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0090] (1) Weigh 30 g of cordierite, 40 g of boron phenolic resin, and 8 g of cage-type organosilicon silsesquioxane, add them into a high-speed mixer and mix to obtain a mixture. The weight average molecular weight of the boron phenolic resin is 1000 to 1500 Daltons.

[0091] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, and molded at 200° C. and a hot pressing pressure of ≥5 MPa for 3.5 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material.

[0092] Example 3

[0093] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0094] (1) Weigh 35 g of zirconium dioxide, 45 g of epoxy resin, and 10 g of cage-type organosilicon silsesquioxane and add them to a high-speed mixer to mix to obtain a mixture. The weight average molecular weight of the epoxy resin is 1,000 to 10,000 Daltons.

[0095] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot pressing pressure of ≥5 MPa for 3 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material.

[0096] For the convenience of description, the high-temperature in-situ ceramicizable porous carbon ceramic material prepared in the above embodiment is referred to as porous carbon ceramic material for short.

[0097] Table 2 High-temperature in-situ ceramic porous carbon ceramic materials prepared from different raw materials

[0098]

[0099]

[0100] Note: C stands for cordierite; Z stands for zirconium dioxide; BPF stands for boron phenolic resin; ER stands for epoxy resin; BPF-BC stands for boron phenolic resin + cage-type organosilicon silsesquioxane + cordierite; ER-BZ stands for epoxy resin + cage-type organosilicon silsesquioxane + zirconium dioxide.

[0101] The materials prepared in Examples 1 to 3 were used as samples to conduct dynamic ablation performance tests.

[0102] Test method: Dynamic ablation test was carried out using a Bunsen burner, with the flame 10 mm away from the sample, the ablation temperature 2500°C, and the ablation time 15 min.

[0103] By comparing the surface morphology of the samples of Examples 1 to 3 after ablation at 2500°C, it can be seen that the surfaces of the samples of Examples 1 to 3 are harder after ablation at 2500°C, and a dense ceramic protective layer is formed on the surface of the carbon layer, which hinders the diffusion of oxygen from the boundary layer into the carbon-based resin matrix, thereby improving the ablation thermal insulation performance of the high-temperature in-situ ceramic porous carbon ceramic material. In addition, the thermal weight loss rate of the samples of Examples 1 to 3 after ablation at 2500°C is less than 5%, and the dimensional change is less than 3%. The surface of the samples remains intact, and no stratification, obvious erosion, or peeling occurs.

[0104] Example 4

[0105] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0106] (1) Weigh 40 g of albite, 50 g of polyimide resin, and 10 g of cage-type organosilicon silsesquioxane and add them to a high-speed mixer to mix to obtain a mixture. The weight average molecular weight of the polyimide resin is 2000 to 3000 Daltons.

[0107] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot pressing pressure of ≥5 MPa for 4 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material.

[0108] Example 5

[0109] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0110] (1) Weigh 40 g of albite, 50 g of polyimide resin, and 10 g of cage-type organosilicon silsesquioxane and add them to a high-speed mixer to mix and obtain a mixture. The weight average molecular weight of the polyimide resin is 4000 to 5000 Daltons.

[0111] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot pressing pressure of ≥5 MPa for 4 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material.

[0112] Example 6

[0113] A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material comprises the following steps:

[0114] (1) Weigh 40 g of albite, 50 g of polyimide resin, and 10 g of cage-type organosilicon silsesquioxane, add them into a high-speed mixer and mix to obtain a mixture. The weight average molecular weight of the polyimide resin is 9,000 to 10,000 Daltons.

[0115] (2) After the mixture is heated to a hot melt state, it is vacuumed to degas, and then placed on a hot press, molded at 200° C. and a hot pressing pressure of ≥5 MPa for 4 hours, and then demolded to obtain a high-temperature in-situ ceramic porous carbon ceramic material.

[0116] Examples 4 to 6 use polyimide resins with different weight average molecular weights to prepare high-temperature in-situ ceramic porous carbon ceramic materials. The sample of high-temperature in-situ ceramic porous carbon ceramic material prepared in Example 4 is recorded as PII; the sample of high-temperature in-situ ceramic porous carbon ceramic material prepared in Example 5 is recorded as PII-50; the sample of high-temperature in-situ ceramic porous carbon ceramic material prepared in Example 6 is recorded as PII-100. Dynamic ablation tests were performed on the three samples of PII, PII-50, and PII-100 to explore the thermal insulation properties of the three materials.

[0117] Test method: Dynamic ablation test was carried out using a Bunsen burner, with the flame 10 mm away from the sample, the ablation temperature 2500°C, and the ablation time 15 min.

[0118] Figure 4 It is the thermal insulation performance curve of the high temperature in-situ porcelainizable porous carbon ceramic material of Example 4 to Example 6. Among them, PII represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 2000 to 3000 Daltons; PII-50 represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 4000 to 5000 Daltons; PII-100 represents the high temperature in-situ porcelainizable porous carbon ceramic material prepared by polyimide resin with a weight average molecular weight of 9000 to 10000 Daltons.

[0119] The side away from the flame is the back side. The general protection requirements for aluminum alloy shells are: the back side temperature is required to be ≤150℃. The annealing temperature of 45# steel is ≤600℃.

[0120] Depend on Figure 4 The results show that the back temperature of the three materials is lower than 120°C within the 50s test time, which meets the protection requirements of general aluminum alloy shells. After 210s of ablation, the back temperature of the three materials is no higher than 164°C, which meets the protection requirements of steel and is much lower than the annealing temperature of 45# steel. This shows that the introduction of co-solvents and ceramic precursors improves the thermal oxidation stability of the materials, thereby improving the ablation resistance and thermal insulation properties of the materials.

[0121] Figure 5 It is the thermal weight loss curve of the high temperature in-situ ceramic porous carbon ceramic material of Example 4 to Example 6.

[0122] The thermal decomposition of polymers is the carbonization and gasification process of their molecules, which determines the ablation and thermal insulation properties of the materials. The thermal decomposition properties of high temperature in-situ ceramic porous carbon ceramics prepared from polyimide resins with different weight average molecular weights were studied by thermogravimetric analysis.

[0123] Figure 5 The results of TG and DTG are summarized. Obviously, the three materials obtained are stable at 400°C and there is no obvious mass loss before this temperature. From 400°C to 580°C, the TGA curve shows a slight mass loss, which may be attributed to the further curing of the polyimide resin. Starting from around 580°C, the TGA curve begins to decline, indicating that the main chain of the polyimide resin begins to gradually decompose. The DTG curve of PII-50 has two degradation peaks in air and only one degradation peak in nitrogen. This phenomenon is due to the participation of oxygen in the thermal cross-linking reaction, forming a more high-temperature resistant protective layer.

[0124] In subsequent studies, the effects of different hot pressing temperatures were also explored. The results show that within the hot pressing temperature range of 160°C to 200°C, as the hot pressing temperature increases, the curing effect is better and the thermal properties of the product are higher. Since the product is a thermosetting polymer, a higher curing temperature will result in a higher degree of crosslinking, so its thermal properties are higher. However, when the hot pressing temperature is greater than 200°C, the carbon-based resin matrix decomposes. When the hot pressing temperature is less than 160°C, the carbon-based resin matrix does not melt, resulting in uneven dispersion of the mixture, the presence of an interface, and poor mechanical properties.

[0125] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-temperature in-situ ceramic porous carbon ceramic material, characterized in that: The following steps are involved: A carbon-based resin matrix and a ceramic precursor are used as the main reaction raw materials. A flux is added, and after mechanical blending, hot pressing is performed in a hot melt state to form a ceramic protective layer on the surface of the carbon layer, thereby obtaining a high-temperature in-situ ceramicizable porous carbon ceramic material. The carbon-based resin matrix is ​​at least one of polyimide resin, aminophenol-formaldehyde resin, boronphenol-formaldehyde resin, bariumphenol-formaldehyde resin, magnesiumphenol-formaldehyde resin, polyurethane, and epoxy resin; The ceramic precursor is at least one of albite, cordierite, silicon carbide and zirconium dioxide.

2. The method for preparing a high temperature in-situ ceramic porous carbon ceramic material according to claim 1, characterized in that: The mass ratio of the carbon-based resin matrix, the ceramic precursor and the flux is 3-4:4-5:0.8-1.

3. The method for preparing a high temperature in-situ ceramic porous carbon ceramic material according to claim 1, characterized in that: The flux is at least one of cage-type organosilicon silsesquioxane, silicon dioxide and bismuth oxide.

4. The method for preparing the high temperature in-situ ceramic porous carbon ceramic material according to claim 1, characterized in that: The conditions for hot pressing molding are: hot pressing temperature of 160°C to 200°C; hot pressing pressure of 5MPa to 15MPa, and hot pressing time of 3h to 4h.

5. The method for preparing the high temperature in-situ ceramic porous carbon ceramic material according to claim 1, characterized in that: Before the hot pressing molding, the process also includes: vacuum degassing the hot melt mixture.

6. A high temperature in-situ ceramic porous carbon ceramic material, characterized in that: The preparation method is as claimed in claim 1.

7. The high temperature in-situ ceramicizable porous carbon ceramic material according to claim 6, characterized in that: The average pore size of the high-temperature in-situ ceramic porous carbon ceramic material is 5nm-100μm.

8. The high temperature in-situ ceramicizable porous carbon ceramic material according to claim 6, characterized in that: The high-temperature in-situ ceramicizable porous carbon ceramic material has a linear ablation rate of -0.05 mm / min and a mass ablation rate of 0.04 g / min.

9. Use of the high-temperature in-situ ceramicizable porous carbon ceramic material according to claim 6 in preparing ablative heat-insulating materials.

10. Use of the high temperature in-situ ceramicizable porous carbon ceramic material according to claim 9 in preparing ablative heat insulation materials, characterized in that: The thermal protection temperature of the ablative insulation material is between 2500℃ and 3800℃.

Citation Information

Patent Citations

  • Ceramic high carbon polymer matrix composite and preparation method thereof

    CN103058632A

  • High-temperature ceramic resin based composite material

    CN106700407A

  • Ceramizable phenolic resin as well as preparation method and application thereof

    CN111349306A

  • Ceramic composition with silsesquioxane polymer

    CN1930225A

  • Flexible ablator for thermal protection

    US10752386B1

Cited By

  • Carbon nanotube reinforced porous carbon ceramic material, preparation method and application

    CN122380824A